Adjustable dielectric properties of BaTiO3 containing MgO inclusions deformable under Spark Plasma Sintering. (1st January 2016) - Epherre, Romain; Lesseur, Julien; Albino, Marjorie; Veber, Philippe; Weibel, Alicia; Chevallier, Geoffroy; Maglione, Mario; Bernard, Dominique; Elissalde, Catherine; Estournès, Claude
Graphical abstract: Abstract: Spark Plasma Sintering (SPS) is an efficient technique to produce highly densified ferroelectric–dielectric composites with good control of the interfaces and microstructures. We present an effective approach based on precursor preparation to produce BaTiO3 /MgO with adjustable hardness for the inclusions. The influence of their rigidity on the sintering composites was investigated and the possibility of being able to tailor the permittivity simply by changing the morphology of the MgO inclusions was demonstrated.